1998
DOI: 10.1515/jpme.1998.26.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal flora in breast- and bottle-fed infants

Abstract: We verified whether an adapted formula, which presents poly-oligosaccharides containing maltose, promotes intestinal implantation of bacterial microflora to the extent that breast milk does, as an epidemiological link exists between newborn feeding methods and infant health. Stool specimens were taken and cultured at the fourth day of life from vaginally born neonates. Twenty-two were breast-fed and 20 were fed with formula. In breast-fed infants, the Bifidobacterium was significantly prevalent expressed in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 25 publications
4
42
1
2
Order By: Relevance
“…Studies have shown differences in the composition of microbiota between breast-fed and formula-fed babies (Rubaltelli et al, 1998;Wold & Adlerberth, 2000). This lack of human milk oligosaccharides in formula-fed pre-term babies may also contribute to NEC pathogenesis.…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…Studies have shown differences in the composition of microbiota between breast-fed and formula-fed babies (Rubaltelli et al, 1998;Wold & Adlerberth, 2000). This lack of human milk oligosaccharides in formula-fed pre-term babies may also contribute to NEC pathogenesis.…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…The present study was designed to investigate the effect of only 0.24 g/dL quite different from those fed with a standard infant for mula [16] . Both Bifidobacteria and Lactobacilli are beneficial to infants.…”
Section: Applicationsmentioning
confidence: 99%
“…Consequently, strict anaerobic bacterial population dominated by bifidobacteria, Clostridium and Bacteroides can be established [55][56][57]. Within the first year of life, the microflora is highly dynamic, but by the age of two years with the introduction of solid foods, the colonic microbiota is considered complete -it stabilizes and resembles that of the adult [58][59][60].…”
Section: Prebiotic Efficacy In Infancy and Childhoodmentioning
confidence: 99%